South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper highlights that cautious monetary and fiscal polices of South Africa during 1997 resulted in a return of financial investor confidence and capital inflows during 1997 and through April 1998. These policies helped the South African economy emerge successfully from the exchange market pressures of 1996 and weather the contagion from the East Asian crisis in the second half of 1997. Throughout 1997 and up until May 1998, inflation and market interest rates fell considerably, net international reserves increased, and the net open forward position of the Reserve Bank was reduced sharply.